Dispute Resolution in Sharia Banking: Challenges and Judicial Reform for Enhanced Legal Certainty - Budi Purnomo; Abdul Aziz; Achmad Achmad; Sugianto Sugianto (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
Sharia banking, a growing sector within Indonesia's civil law system, operates under Islamic legal principles while serving diverse clients, both Muslim and non-Muslim. This research explores the challenges in resolving disputes within Sharia banking, emphasizing the need for judicial integration. The study utilizes both a legislative and conceptual approach, examining relevant laws and regulations, while developing a comprehensive framework for judicial reform. Results indicate that despite the Religious Courts' authority over Sharia economic disputes, jurisdictional ambiguity persists, often leading to confusion. Additionally, the study highlights the importance of alternative dispute resolution (ADR), such as mediation and arbitration, which aligns with Sharia principles and offers a faster, cost-effective means of resolving disputes. The findings suggest that a unified judicial system, with the Religious Courts as the sole authority in Sharia economic disputes, coupled with strengthened ADR mechanisms, would promote legal certainty and support the sustainable development of Indonesia's Sharia banking sector. Implications include recommendations for enhancing regulatory frameworks, improving judicial competence, and fostering collaboration between regulatory authorities, industry stakeholders, and the judiciary to ensure fair and efficient dispute resolution.